Impact of Bifidobacterium bifidum MIMBb75 on mouse intestinal microorganisms. Issue 2 (19th April 2013) - Singh, Natasha; Arioli, Stefania; Wang, Angela; Villa, Christopher R.; Jahani, Raha; Song, Ye Seul; Mora, Diego; Guglielmetti, Simone; Comelli, Elena M.
Abstract: Bifidobacterium bifidum MIMBb75 is a recently identified probiotic. However, its distribution along the intestine and impact on resident microbiota is unknown. Herein, we established a quantitative real‐time polymerase chain reaction assay targeting the B. bifidum ‐specific BopA region for the quantification of B. bifidum in feces and used this assay to investigate transit of B. bifidum MIMBb75 through the murine intestine. We also analyzed the consequential impact on resident microbial cohorts. C57BL/6J mice were daily gavaged with 0.2 mL of either sterile PBS or PBS containing 10 8 colony‐forming units of B. bifidum MIMBb75 for 2 weeks, after which intestinal contents and fecal samples were analyzed for microbial compositional changes. Bifidobacterium bifidum MIMBb75 was able to transiently colonize the murine intestine, with the predominant niche being the ceco‐proximal colonic region. Region‐specific effects on host microbiota were observed including decreased levels of Clostridium coccoides in the cecum, increased levels of bifidobacteria in the proximal and distal colon, total bacteria and Clostridium leptum in the proximal colon, and of C. coccoides in the feces. These findings suggest that probiotic properties of B. bifidum MIMBb75 may partially depend on its ability to at least transiently colonize the intestine and impact on the resident microbial communities at various intestinal loci.